The effect of discipline and work environment on employee performance at New Hollywood Hotel Pekanbaru - Annajmi Mulki Aika; Auzar Ali; Yulizar Baharuddin (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the discipline and work environment on employee performance at the New Hollywood Hotel Pekanbaru, the analysis used in this study is multiple linear analysis. The population in this research is all 42 employees at New Hollywood Hotel Pekanbaru. This is called the census technique. The data collection technique used is the method of observation, questionnaires and file research. Hypothesis testing was carried out with the F test and t test. Based on the results of the study, it can be concluded that simultaneously discipline and work environment on employee performance, while the partial test of discipline and work environment has an effect on employee performance, the close relationship between the independent variable and the dependent variable is very strong with the contribution of the independent variable to the dependent variable of 80.1%. The results of this analysis indicate that discipline and work environment have a significant simultaneous and partial effect on employee performance at the New Hollywood Hotel Pekanbaru.